CH3CN on Si(001) : adsorption geometries and electronic structure - Miotto, Ronei (2004)
In this work we employ the state of the art pseudopotential method, within a generalized gradient approximation to the density functional theory, to investigate the adsorption process of acetonitrile on the silicon surface. Our first-principles calculations indicate that CH3CN adsorbs via a [2+2] cycloaddition reaction through the CºN group with an adsorption energy around 35 kcal/mol, close to the 30 kcal/mol estimated by Tao and co-workers. The electronic structure and the surface states calculated for the adsorbed system are also discussed.